HUBUNGAN LATAR BELAKANG SOSIAL EKONOMI ORANG TUA DENGAN HASIL BELAJAR SISWA KELAS V SD NEGERI SE-GUGUS 7 KECAMATAN TAMPAN KOTA PEKANBARU - Sry Suryati; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this research was effected by the results of the initial interview conducted in one homeroom as saying that many children whose parents had low economy obtain a high learning outcomes, while students who are her parents ' economic high gain low learning outcomes. Whereas in order that students can earn a high learning results. parents should be able to meet all that can support learning activities of students, as it needs anyway, intensity of support facilities and infrastructure or facilities learn in school or in the the House. Learning facilities that can only be fulfilled if parents have enough money. The main objective of this research is to know the relationship between the socioeconomic background of the parents with the results of student learning. This research is carried out In State Elementary School Se-Gugus 7 of Tampan District of Pekanbaru City 3 States elementary school. The State that is, the States elementary school 110 Pekanbaru, the States elementary school 164 Pekanbaru, and the States elementary school 191 Pekanbaru, with total sample as many as 74 students, using the technique of sampling sampling cluster. Research data were analyzed using the Spearmen correlation Rank test with significant level α = 0.05. the results of the analysis of data obtained tcount of 4.252 and ttable of 1.993. So tcount > ttabel or 4,436 > 1.993. the results show that there is a significant relationship between the socioeconomic background of parents with learning outcomes students Then rhocount of = 0448 which means it has a degree of relationship that is strong enough and its contribution of 20.1%.Key words : Socio-economic background of the parents, Student learning outcomes